IMPACT OF TEACHER WELFARE ON IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION - Aidil Akhyar; Hasbiyallah Hasbiyallah; Aan Hasanah; Hasan Basri; Uus Ruswandi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
Teacher welfare is indeed an important thing, because teachers need guarantees for the work they do. To Teachers need appreciation for their duties. Teachers have the responsibility to create quality learning in order to facilitate the achievement of the objectives of the subjects. The research method used in this research is a qualitative method. Teacher welfare is a guide for teachers to continue to be enthusiastic in carrying out their duties. Teachers of Islamic Religious Education subjects, will be happy if the clarity of the welfare of their work is guaranteed either by the government, or by the private sector if they are committed. The indicators of learning quality consist of: appropriate learning design and focus on standards, delivery of high quality learning, learner-centered, increasing students' activeness in learning, evaluating students, implementing positive behavior management strategies, clarity of learning for students. Learning has clear objectives, if the teacher can organize it well, the learning objectives will be achieved, otherwise it will not be achieved. With the existence of teacher welfare prepared by the government and the private, teacher must be more enthusiastic in teaching, learning will be more interesting, not boring. Innovation in learning Islamic Religious Education needs to be done so that it is of higher quality.